PERAN GURU PENDIDIKAN AGAMA HINDU DALAM MENCEGAH DAN MENANGANI KASUS PERUNDUNGAN (STUDI KASUS DI SMP NEGERI SE-KECAMATAN BANGLI - I Dewa Putu Suyadnya; Ida Ayu Tary Puspa; Kadek Arya Prima Dewi PF (JAPAM (Jurnal Pendidikan Agama), 2025)
Bullying in the school environment remains a critical issue that threatens students’ sense ofsafety and comfort in the learning process. This study aims to analyze the role of Hindu ReligiousEducation teachers in preventing and addressing bullying, identify the challenges they face, anddescribe the efforts undertaken to create a violence-free school environment. A qualitative approachwith a case study design was used, involving five public junior high schools in Bangli District throughin-depth interviews, observations, and documentation. The findings reveal that Hindu ReligiousEducation teachers fulfill four key roles. First, as educators, they deliver moral teachings and Hinduvalues such as ahimsa (non-violence), karuna (compassion), and tat twam asi (I am you, you are me)to shape students' character. Second, as moral exemplars, they serve as role models through dailybehavior and attitudes. Third, as spiritual mentors, they guide students to develop inner disciplineand avoid violent behavior. Fourth, as community liaisons, they bridge communication amongschools, students, parents, and the wider community. The main challenges encountered includestudents’ limited understanding of the consequences of bullying, the influence of peer socialenvironments, and the negative impacts of social media. In response, Hindu Religious Educationteachers undertake various strategic actions, including early intervention upon detecting bullying,providing support for both perpetrators and victims, coordinating with school authorities, andimplementing preventive strategies by integrating religious values into learning and student activitie.